Synthetic, Structural and Antimicrobial Studies of Some Substituted 2,6-Diphenyl-1-aza-7-oxa-4-spiro[2,5]octanes - Jambulingam, M.; Sathish, Asha; Vasanthakumar, J.; Rakkiyappan, K. (Asian Journal of Chemistry, 2016)
Different methyl substituted 2,6-diphenyl piperidones have been synthesized and subjected to the reaction with dimethyl sulphoxonium methyl ylide in the presence of potassium tertiary butoxide for the preparation of the corresponding spiro oxiranes. The structures of the products have been confirmed by various physical techniques.